The Clean Hydrogen Economy and Saudi Arabia: Domestic Developments and International Opportunities (Routledge Explorations in Environmental Economics, 2024)
This book provides a first-of-its-kind analysis of the emerging global hydrogen economy from the vantage point of one of the world's biggest energy providers: Saudi Arabia. In 2021, and within the context of the Circular Carbon Economy framework, Saudi Arabia announced its goal to reach net-zero carbon emissions by 2060 and produce a substantial amount of clean hydrogen annually by 2030. The Kingdom is optimally situated geographically between the major demand markets in Europe and North Asia, from where it can leverage clean hydrogen exports as a potential tool to become a player of strategic importance and successfully diversify its economy under its Vision 2030 program. More broadly, the book charts a course for fossil fuel-exporting countries such as Saudi Arabia to carve a competitive position for themselves over the forthcoming decades using clean hydrogen as a catalyst for the energy transition. With contributions from global energy experts, the chapters in this book provide a multifaceted analysis of the "who," "what," "where," and 'why' related to clean hydrogen development within and beyond Saudi Arabia. Collectively, the contributions analyze the countries and regions relevant to Saudi Arabia in terms of dedicated hydrogen policies, projects, and approaches that aim to incentivize production and demand in an increasingly carbon-constrained world. The book is a timely, unique and an indispensable resource for practitioners and students of energy, geopolitics, and climate policy working on hydrogen in academia, applied research, national government bodies, and international organizations.